62.7k views
2 votes
Solve 2sin(2x) - 2sinx +2sqrt3 cosx - sqrt3 = 0

2 Answers

5 votes

Answer:

x = +/-pi/3 or x = -pi/3 or (4/3)pi

Explanation:

2sin(2x)-2sinx+2sqrt3cosx-sqrt3 = 0

4sinxcosx - 2sinx + 2sqrt(3)cosx - sqrt(3) = 0

2sin(x)[2cos(x)-1] + sqrt(3)[2cos(x)-1] = 0

[2cos(x)-1][2sin(x)+sqrt(3)] = 0

2cos(x)-1 = 0 or 2sin(x)+sqrt(3) = 0

cos(x) = 1/2 or sin(x) = -sqrt(3)/2

x = +/-pi/3 or x = -pi/3 or (4/3)pi

User Bruno Bronosky
by
5.3k points
4 votes

Answer:

2sin(2x)-2sinx+2sqrt3cosx-sqrt3 = 0

-----

4sin(x)cos(x) - 2sin(x) + 2sqrt(3)cos(x) - sqrt(3) = 0

-----

Factor:

2sin(x)[2cos(x)-1] + sqrt(3)[2cos(x)-1] = 0

-----

[2cos(x)-1][2sin(x)+sqrt(3)] = 0

Solve:

2cos(x)-1 = 0 or 2sin(x)+sqrt(3) = 0

cos(x) = 1/2 or sin(x) = -sqrt(3)/2

x = +/-pi/3 or x = -pi/3 or (4/3)pi

hope this helps!

User Daddy Warbox
by
5.4k points